2021
DOI: 10.3389/fnagi.2020.622360
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Hyperreactivity Evolved to Immunosuppression in the Hippocampus of a Mouse Model of Accelerated Aging and Alzheimer’s Disease Traits

Abstract: Neuroinflammation is a risk factor for Alzheimer’s disease (AD). We sought to study the glial derangement in AD using diverse experimental models and human brain tissue. Besides classical pro-inflammatory cytokines, we analyzed chitinase 3 like 1 (CHI3L1 or YKL40) and triggering receptor expressed on myeloid cells 2 (TREM2) that are increasingly being associated with astrogliosis and microgliosis in AD, respectively. The SAMP8 mouse model of accelerated aging and AD traits showed elevated pro-inflammatory cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 89 publications
2
12
0
Order By: Relevance
“…Furthermore, we employed additional quantitative technologies, including the same immunoassay that is widely used for CSF analysis, which showed again no differences on YKL-40 levels between AD or FTLD and controls post-mortem brain. It is worth noting that a recent study showed no difference in CHI3L1 mRNA post-mortem tissue from early-onset AD cases, which was attributed to the younger age of these patients [ 54 ]. In line with our findings, a recent mass-spectrometry-based study detected YKL-40 changes in the CSF of AD patients but not in post-mortem tissue [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we employed additional quantitative technologies, including the same immunoassay that is widely used for CSF analysis, which showed again no differences on YKL-40 levels between AD or FTLD and controls post-mortem brain. It is worth noting that a recent study showed no difference in CHI3L1 mRNA post-mortem tissue from early-onset AD cases, which was attributed to the younger age of these patients [ 54 ]. In line with our findings, a recent mass-spectrometry-based study detected YKL-40 changes in the CSF of AD patients but not in post-mortem tissue [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, polarization of microglia to a reactive phenotype is an early event after Aβ 42 accumulation in these mice. TREM2 has also been found increased in the cerebral cortex of autosomal dominant AD patients [ 55 ]. Microglia play an important role in the innate immune response of the brain and their phenotypic changes may protect against neurodegeneration or worsen it when chronically activated [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…TREM2 has also been found increased in the cerebral cortex of autosomal dominant AD patients [ 55 ]. Microglia play an important role in the innate immune response of the brain and their phenotypic changes may protect against neurodegeneration or worsen it when chronically activated [ 55 , 56 ]. Interestingly, maternal TPPU maintained low levels of Trem2 in both 5XFAD and WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, microglia may get out of control and out of balance resulting in augmenting brain damage or sustaining chronic pathologies like neuroinflammation and inducing or enhancing neurodegeneration [ 28 , 35 ]. In such case, microglia may enhance brain aging [ 59 , 80 , 128 , 196 , 221 , 222 , 223 , 224 , 225 , 226 ].…”
Section: The Role Of Microglia In Viral Brain Infections Accelerating Brain Agingmentioning
confidence: 99%